Radiographic film system classification and noise characterisation by a camera-based digitisation procedure. (April 2020) - Eckel, Sebastian; Zscherpel, Uwe; Huthwaite, Peter; Paul, Nicolas; Schumm, Andreas
Abstract: Extracting statistical characteristics from radiographic films is vital for film system classification and contrast sensitivity evaluation and serves as a basis for film noise simulation. A new method for digitising radiographic films in order to extract these characteristics is presented. The method consists of a camera-based setup and image processing procedure to digitise films. Correct optical density values and granularity can be extracted from the digitised images, which are equal to results obtained by standardised measurement procedures. Specific statistical characteristics of film noise are theoretically derived and subsequently verified by the obtained data, including characteristics such as Gaussianity and spatial spectral characteristics of the optical density fluctuations. It is shown that the presented method correctly measures the granularity of film noise and can therefore replace time-consuming microdensitometer measurements traditionally required for film system classifications. Additionally, the inherent unsharpness of film systems was investigated and compared with literature data. This comparison serves as another validation approach of the presented method. Highlights: A new method for digitisation of radiographic films is presented. Film noise characteristics are investigated by means of the new procedure. The digitisation method replaces time-consuming microdensitometer measurements. It provides an alternative method for film system characterisation.